Antitumor responses stimulated by dendritic cells are improved by triiodothyronine binding to the thyroid hormone receptor β - Alamino, Vanina Alejandra (2015)
Bidirectional cross-talk between the neuroendocrine and immune systems orchestrates immune responses in both physiologic and pathologic settings. In this study, we provide in vivo evidence of a critical role for the thyroid hormone triiodothyronine (T3) in controlling the maturation and antitumor functions of dendritic cells (DC). We used a thyroid hormone receptor (TR) β mutant mouse (TRβPV) to establish the relevance of the T3-TRβ system in vivo. In this model, TRβ signaling endowed DCs with the ability to stimulate antigen-specific cytotoxic T-cell responses during tumor development. T3 binding to TRβ increased DC viability and augmented DC migration to lymph nodes. Moreover, T3 stimulated the ability of DCs to cross-present antigens and to stimulate cytotoxic T-cell responses. In a B16-OVA mouse model of melanoma, vaccination with T3-stimulated DCs inhibited tumor growth and prolonged host survival, in part by promoting the generation of IFNγ-producing CD8(+) T cells. Overall, our results establish an adjuvant effect of T3-TRβ signaling in DCs, suggesting an immediately translatable method to empower DC vaccination approaches for cancer immunotherapy.